MARCUS AURELIUS – IDEAS OF THE LAST GREAT STOIC AS A FOUNDATION OF DIFFERENT NATURAL LAW THEORIES - Avramović, Dragutin (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Literature on Marcus Aurelius is quite controversial. A part of scholars fully deny that he was a stoic philosopher, more moderate scholars are classifying him as an emperor to whom stoic philosophy was only a personal philosophy (a life standing), while the third group perceive Marcus Aurelius as the last influential stoic philosopher. In the first place, the author examines the question if it is suitable to denote Aurelius as an emperor-philosopher, suggesting that Aurelius was primarily a philosopher, and only secondarily an emperor. The central part of the paper analyses influences of Aurelius’ ideas upon later natural law theory. The author finds that his thoughts are partially accepted (and applied to a certain degree) by different, even contradictory natural law theories (Christian and rational). He additionally considers same fact as a proof that Aurelius was really a great stoic philosopher who succeeded to build a bridge between something that looked impossible before – between faith and ratio. The author analyses life and work of Aurelius, his achievements in stoic philosophy, the influence that he has made both upon medieval Christian natural law theory and upon rational natural law theory as well. Finally, the author particularly points to Aurelius` specific way in compromising two different extremes – the faith and the ratio. Consequently, he concludes that it is most justifiable to treat and label Marcus Aurelius as a philosopher-emperor.